Pengaruh Religiusitas, Islamic Branding dan Literasi Keuangan Syariah terhadap Keputusan Generasi Milenial Muslim dalam Memilih Jasa Bank Syariah di Kota Banjarmasin - Marhusin; Raudah; Mariyam (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: CNBC data shows that the level of Islamic financial inclusion is still very low compared to conventional financial services. Users of these services are mostly Muslim millennials. Whereas the millennial generation who already know the Islamic Bank system still chooses Conventional Banks. By all means there are underlying factors. So this study aims to determine whether Religiosity, Islamic Branding and Islamic Financial Literacy influence the decisions of the Muslim millennial generation in choosing Islamic Bank services in Banjarmasin City. This research is a field research with a quantitative approach. The population in this study is the Muslim millennial generation in Banjarmasin City as many as 288,755. The sampling technique used Random Sampling with the Slovin formula which produced a sample of 100 people. Data collection is by distributing questionnaires made with a Likert scale and analyzed using multiple linear regression using the help of IBM SPSS 26 for windows. The results of the study based on the t-test and F-test prove that, Religiosity has a positive and significant partial effect on the decision of the Muslim millennial generation in choosing Islamic Banking services in Banjarmasin City. Islamic Branding has a positive and significant partial effect on the decision of the Muslim millennial generation in choosing Islamic Banking services in Banjarmasin City and Islamic Financial Literacy has a positive and significant partial effect on the decision of the Muslim millennial generation in choosing Islamic Banking services in Banjarmasin City. Simultaneously (together) Religiosity, Islamic Branding and Islamic Financial Literacy have a significant and positive effect on the decision of the Muslim millennial generation in choosing Islamic Banking services in Banjarmasin City Keywords: Religiosity, Islamic Branding and Sharia Financial Literacy, Decisions